A rare initial presentation: gastrointestinal symptoms in systemic lupus erythematosus and its differential diagnosis - Abdul Hadi, Azwanis; Abd Latip, Nurul Akmal; Ismail, Nizamuddin (2021)
Diarrhoea and vomiting  acute gastroenteritis  Typical presentations of SLE: skin manifestation and joint pain.  Gastrointestinal (GI) symptoms are rare presentation of SLE at the onset of diagnosis.